Prom mom ebook A novel. - Lippman, Laura (2023)
"Well-plotted, well-written, clear-eyed. I never saw the end coming. There's a hell of a one-two punch waiting for you." —Stephen King New York Times bestseller Laura Lippman tells the story of Amber Glass, desperately trying to get away from her tabloid past but compulsively drawn back to the city of her youth and the prom date who destroyed everything she was reaching for. Amber Glass has spent her entire adult life putting as much distance as possible between her and her hometown of Baltimore, where she fears she will forever be known as "Prom Mom"—the girl who allegedly killed her baby on the night of the prom after her date, Joe Simpson, abandoned her to pursue the girl he really liked. But when circumstances bring Amber back to the city, she realizes she can have a second chance—as long as she stays away from Joe, now a successful commercial real estate developer, married to a plastic surgeon, Meredith, to whom he is devoted. The problem is, Amber can't stay away from Joe. And Joe finds that it's increasingly hard for him to ignore Amber, if only because she remembers the boy he was and the man he said he was going to be. Against the surreal backdrop of 2020 and early 2021, the two are slowly drawn to each other and eventually cross the line they've been trying not to cross. And then Joe asks Amber to help him do the unthinkable . . . and she must decide if she is willing to let their toxic and dangerous past repeat itself.